Visualization and modeling of forest fire propagation in Patagonia. (December 2022) - Denham, Mónica M.; Waidelich, Sigfrido; Laneri, Karina
Abstract: Fire propagation is a big concern all over the world. Visualization is a valuable tool to test possible different scenarios for fire spread, specially for designing strategies for fire control, mitigation and management. We present a parallel High-Performance Computing (HPC) forest fire simulator with an interactive and intuitive user interface that offers several functionalities to the user. The visualization interface allows to choose the propagation model of preference, the scenario of interest, as well as numerous simulation features including firebreaks and ignition points. We show some of the outputs for two different mathematical models for fire spreading. The simulator was developed with an open source philosophy in the framework of Faster Than Real Time (FTRT) applications thinking on its possible use in the field during a forest fire propagation. It can be run in Linux (Ubuntu) and Windows Operating Systems and for portability purposes the simulator was also implemented on a NVIDIA Jetson Nano. Graphical abstract: Highlights: The Simulador de Incendios Patagonia (SIP) is a High-Performance Computing and Real Time application. SIP was programmed for GPGPUs, for Linux (Ubuntu), Windows and NVIDIA Jetson Nano hardware. Different scenarios can be used for fire propagation and visualization (calibration needed). The Fire Weather Index (FWI) and the resulting fire risk map are embedded in the SIP. Two mathematical models for fire propagation are implemented within the SIP application.